Comparative outcomes and predictive assessment of trifecta in open, laparoscopic, and robotic-assisted partial nephrectomy cases with renal cell carcinoma: A 10-year experience at ramathibodi hospital - Chaichant Soisrithong (2022)
Purpose: To compare perioperative and trifecta outcomes of open partial nephrectomy (OPN), laparoscopic partial nephrectomy (LPN), and robotic-assisted laparoscopic partial nephrectomy (RPN) in patients with small renal mass at Ramathibodi Hospital, and to determine predictive factors in connection with trifecta. Methods: We retrospectively reviewed 141 patients who underwent partial nephrectomy by eight experienced surgeons from January 2009 to December 2018. Baseline preoperative characteristics, postoperative and trifecta outcomes of the three treatment modalities were compared and analyzed. Univariate analysis was performed to determine predictive factors for trifecta achievement. Results: A total of 70 patients had complete data available. Eighteen OPN, 11 LPN and 41 RPN cases were identified and reviewed. All preoperative and perioperative parameters were similar, except for operative time, which was significantly shorter in the OPN group compared with those undergoing LPN and RPN (135 vs 189 and 225 min, respectively; p-value = 0.001). Of these 70 patients, 59 were deemed eligible for and included in trifecta analysis, which revealed similar trifecta outcomes (64.29%, 45.45%, and 64.71% in the OPN, LPN, and RPN groups, respectively; p-value = 0.388). Univariate analysis showed that length of hospital stay was a negative associated factor for trifecta achievement (p-value = 0.007, 95% CI = 0.619 (0.44–0.88)). Conclusion: Although OPN displayed the shortest operative time, the trifecta achievement rate was not significantly different among the three groups. The sole parameter, which was negatively associated with trifecta outcome achievement, was the length of hospital stay.